Cost Analysis of Health Examination Screening Program for Ischemic Heart Disease in Active-Duty Military Personnel in the Middle-Income Country - Simic, Radoje; Ratkovic, Nenad; Dragojevic Simic, Viktorija; Savkovic, Zorica; Jakovljevic, Mihajlo; Peric, Vitomir; Pandrc, Milena; Rancic, Nemanja (Frontiers in Public Health, 2021)
Cardiovascular diseases, including ischemic heart disease, are the most common causes of morbidity and death in the world, including Serbia, as a middle-income European country. The aim of the study was to determine the costs of preventive examinations for ischemic heart disease in the active-duty military personnel. This is a retrospective cost-preventive study which included 738 male active military personnel, aged from 23-58. The costs of primary prevention of ischemic heart disease in this population were investigated. Out of 738 subjects examined, arterial hypertension was detected in 101 subjects (in 74 of them arterial hypertension was registered for the first time, while 27 subjects were already subjected to pharmacotherapy for arterial hypertension). Average costs of all services during the periodic-health-examination screening program were €76.96 per subject. However, average costs of all services during the periodic-health-examination screening program for patients with new-found arterial hypertension and poorly regulated arterial hypertension were €767.54 per patient and €2,103.63 per patient, respectively. Since periodic-health-examination screening program in military personnel enabled discovery of not only patient with new-found arterial hypertension, but also regular monitoring of those who are already on antihypertensive therapy, significant savings of €690.58 per patient and €2,026.67 per patient can be achieved, respectively. As financial resources for providing health care in Serbia, as a middle-income country are limited, further efforts should be put on screening programs for ischemic heart disease due to possible significant savings.